2012
DOI: 10.1038/jcbfm.2012.150
|View full text |Cite
|
Sign up to set email alerts
|

PHLPP1 Gene Deletion Protects the Brain from Ischemic Injury

Abstract: A recently discovered protein phosphatase PHLPP (PH domain Leucine-rich repeat Protein Phosphatase) has been shown to dephosphorylate Akt on its hydrophobic motif (Ser473) thereby decreasing Akt kinase activity. We generated PHLPP1 knockout (KO) mice and used them to explore the ability of enhanced in vivo Akt signaling to protect the brain against ischemic insult. Brains from KO mice subjected to middle cerebral artery occlusion (MCAO) for 2 hours showed significantly greater increases in Akt activity and les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…PHLPP1 KD increased AKT but not ERK activation in astrocytes under serum growth conditions (i.e., 10% FBS). This is consistent with work of Chen et al (2013), who showed that astrocytes isolated from PHLPP1 KO mice had higher AKT but not ERK phosphorylation after acute IGF-1 stimulation.…”
Section: Phlpp1 Inhibition In Neurons Versus Astrocytes: Implicationssupporting
confidence: 92%
See 3 more Smart Citations
“…PHLPP1 KD increased AKT but not ERK activation in astrocytes under serum growth conditions (i.e., 10% FBS). This is consistent with work of Chen et al (2013), who showed that astrocytes isolated from PHLPP1 KO mice had higher AKT but not ERK phosphorylation after acute IGF-1 stimulation.…”
Section: Phlpp1 Inhibition In Neurons Versus Astrocytes: Implicationssupporting
confidence: 92%
“…However, ERK activation may not be detrimental in all brain injury paradigms. PHLPP1 KO mice were recently shown to have reduced brain infarct volumes after stroke injury (Chen et al, 2013). Administering an AKT inhibitor before ischemia completely reversed the protective KO phenotype.…”
Section: Phlpp Inhibitors Are Promising New Neuroprotective Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…PHLPP1 exists in neurons in two isoforms, PHLPP1α and PHLPP1β, which are synthesized as splice variants of the same gene and share amino acid sequence homology but differ in size (140 kDa and 190 kDa, respectively). The PHLPP1α isoform dephosphorylates Akt in neurons and its downregulation is linked with a reduced infarct volume in brain ischemia, as found in a transgenic animal model lacking PHLPP1 subjected to MCAO (Chen et al, 2013). On the other hand, PHLPP1β binds and traps the small GTP-binding protein Ras in its inactive form, inhibiting the phosphorylation of ERK and its downstream signaling activity ( Figure 2) (Shimizu et al, 2007;Wang et al, 2013;Wang et al, 2014b).…”
Section: Calpain Activation Mediated By Extrasynaptic Nmdarmentioning
confidence: 94%